Prevalence and risk factors of disordered eating risk among Yemeni medical students: A national multicenter cross-sectional study - Naji Al-bawah; Mohamed Baklola; Anas H. Khalifeh; Ahmed Al-Eryani; Anas Zakarya Nourelden; Saif Alaribi; Ehab Sharyan; Fayda Al-wesabi; Aaida Al Wesabi; Ahdab Al-Jaberi; Sama Shamsan; Ahmed Abdulmughni; et al. (PLoS ONE, 2026)
Background Disordered eating behaviors represent an important mental health concern among medical students, who are exposed to substantial academic and psychological stressors. Data on disordered eating risk in Yemen remain limited. This study aimed to estimate the prevalence of disordered eating risk among Yemeni medical students and to examine associated sociodemographic, lifestyle, medical, and psychological factors. Methods A national multicenter cross-sectional study was conducted between June and July 2025 across fifteen Yemeni medical colleges. Undergraduate students completed a structured, self-administered online questionnaire using a convenience sampling approach. Disordered eating risk was assessed using the Eating Attitudes Test (EAT-26), with a cutoff score of ≥20. Additional items assessed sociodemographic characteristics, lifestyle factors, chronic medical conditions, and self-reported psychiatric diagnoses. Multivariable logistic regression was performed to examine factors associated with disordered eating risk. Results A total of 3,540 students participated. Overall, 30.4% screened positive for disordered eating risk. Disordered eating risk was associated with food insecurity, parental perception of being overweight, weight dissatisfaction, type 1 diabetes mellitus, past suicide attempts, and several self-reported psychiatric conditions, including post-traumatic stress disorder, obsessive compulsive disorder, social anxiety disorder, bipolar disorder, schizophrenia, and major depressive disorder. Weight satisfaction was associated with lower odds of risk. Additionally, 31.6% of participants reported a prior self-reported diagnosis of an eating disorder, which was not independently verified. Conclusion Disordered eating risk was common among Yemeni medical students and was associated with multiple sociodemographic, medical, and psychological factors. Given the cross-sectional design and reliance on self-reported data, causal relationships cannot be established. The findings suggest that consideration may be given to screening and supportive mental health resources within medical training institutions.